PENGEMBANGAN MODEL LATIHAN PUKULAN FOREHAND PADA SISWA EKSTRAKURIKULER TENIS MEJA DI SMA ISLAM AZ-ZAHRAH PALEMBANG - Fahrulrozi; Endrawan, I Bagus; Atesya Kesumawati, Selvi; Meliyanti, Selvi (JURNAL ILMU KEOLAHRAGAAN, 2025)
The lack of varied and targeted training methods has led to suboptimal forehand stroke performance among table tennis extracurricular students at SMA Islam Az-Zahrah Palembang. This study aimed to design and develop an effective forehand drill training model to address this issue. Using a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the product was validated by a table tennis expert, a coaching science expert, and a certified coach. Validation results indicated a high level of validity (average score = 0.94). Small-scale trials with 10 students achieved an average score of 87.4%, while large-scale trials with 30 students scored 95.16%, both categorized as “very good.” The findings demonstrate that the developed model is valid, practical, and effective in improving the accuracy, consistency, and coordination of forehand strokes in table tennis. It can serve as a reference for coaches and physical education teachers in designing structured and engaging training sessions.